Fluoroquinolone-associated suspected tendonitis and tendon rupture: A pharmacovigilance analysis from 2016 to 2021 based on the FAERS database - Shu, Yamin; Zhang, Qilin; He, Xucheng; Liu, Yanxin; Wu, Pan; Chen, Li (Frontiers in Pharmacology, 2022)
Objective: This study was to scientifically and systematically explore the association between fluoroquinolones (ciprofloxacin, levofloxacin and moxifloxacin) and tendonitis and tendon rupture through the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Disproportionality analysis was used to quantify the signals of fluoroquinolones-associated suspected tendonitis and tendon rupture based on the FAERS data from January 2016 to March 2021. Clinical characteristics, the onset time, oral and intravenous administrations and the serious outcomes of fluoroquinolone-associated tendonitis and tendon rupture were further analyzed. Results: Out of 35,667 fluoroquinolones-associated adverse events recorded in the FAERS database during the study period, 1771 tendonitis and 1018 tendon ruptures induced by fluoroquinolones as the suspected drug were analyzed, with a median age of 49.88 to 63.87 years. All three fluoroquinolones detected positive signals of tendonitis and tendon rupture in the four methods. Ciprofloxacin had the strongest statistical association with tendonitis with the highest positive signal values (ROR 98.50, PRR 93.25, IC 6.15, EBGM 76.80), while it was levofloxacin with tendon rupture (ROR 76.38, PRR 73.75, IC 5.84, EBGM 63.89). Compared with ciprofloxacin and levofloxacin, moxifloxacin was relatively weakly associated with tendonitis and tendon rupture. Oral fluoroquinolone-induced tendonitis and tendon rupture had a stronger signal strength than intravenous administration. The majority of fluroquinolone-related suspected tendonitis and tendon rupture tended to occur within a few days or 1 month. As for the disability rate of tendonitis, ciprofloxacin counted the highest (n=461, 50.94%), with moxifloxacin the lowest (n=20, 29.41%). Conclusions: Fluoroquinolone-induced tendonitis and tendon rupture preferred to occur early and might result in serious outcomes. Our study provided valuable references for early identification of the risk of fluoroquinolone-induced tendonitis and tendon rupture.